2013
DOI: 10.1161/circep.113.000553
|View full text |Cite
|
Sign up to set email alerts
|

Conundrum of Sudden Cardiac Death

Abstract: e58T he cause of sudden cardiac death (SCD) in a young patient without any previous cardiac history can oftentimes be challenging, particularly if there are ≥2 equally plausible but improbable pathogenesis. As part of a thorough evaluation, electrophysiological, anatomic/functional, and genetic testing results may be illuminating but at other times can be misleading unless the nuances of test results and their interpretation are fully appreciated. We report a case of a patient who survived an out-of-hospital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We previously reported that transgenic mice expressing the truncated N-ELC (Δ43 mice) display near-physiological cardiac remodeling with an increase in left ventricular (LV) wall thickness but no changes in cardiac morphology or function or in myofilament contraction/relaxation parameters are observed ( Sitbon et al, 2020 ). On the other hand, pathological hypertrophy due to hypertrophic cardiomyopathy (HCM) or restrictive cardiomyopathy (RCM) is characterized by interstitial fibrosis, myofilament disarray, reduced LV cavity, and impaired heart’s relaxation phase and can lead to diastolic dysfunction and sudden cardiac death ( Seidman and Seidman, 1998 ; Spirito et al, 2000 ; Arad et al, 2002 ; Ip et al, 2013 ). RCM is additionally manifested by biatrial enlargement, increased stiffness of the LV wall with no increase in wall thickness ( Kushwaha et al, 1997 ; Yuan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that transgenic mice expressing the truncated N-ELC (Δ43 mice) display near-physiological cardiac remodeling with an increase in left ventricular (LV) wall thickness but no changes in cardiac morphology or function or in myofilament contraction/relaxation parameters are observed ( Sitbon et al, 2020 ). On the other hand, pathological hypertrophy due to hypertrophic cardiomyopathy (HCM) or restrictive cardiomyopathy (RCM) is characterized by interstitial fibrosis, myofilament disarray, reduced LV cavity, and impaired heart’s relaxation phase and can lead to diastolic dysfunction and sudden cardiac death ( Seidman and Seidman, 1998 ; Spirito et al, 2000 ; Arad et al, 2002 ; Ip et al, 2013 ). RCM is additionally manifested by biatrial enlargement, increased stiffness of the LV wall with no increase in wall thickness ( Kushwaha et al, 1997 ; Yuan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%